Do Increasing Levels of Education Contribute to Individualist or Collectivist Orientations? Evidence from the U.S. General Social Survey (Higher Education Politics and Economics, 2025)
While prior research has examined the connection between civic engagement and collectivist views, the present study considers to what extent years of education have been associated with more collectivistic views. This study analyzed data from the 2021 United States General Social Survey. Results suggested that more years of education was associated with believing that the government should do more for Black people and that the government should do move overall (in a scaled average of individualism/collectivism). Specific demographic factors were associated with more collectivist or individualistic views. Implications for program and policy development within higher education are considered.